Efeitos da somatotropina recombinante bovina na taxa de concepção, composição celular do corpo lúteo e morfometria das glândulas endometriais em vacas de corte - Costa, Natália Paulozzi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
cows treated with recombinant bovine somatotropin (bST) have higher conception rate. It was found that maternal and embryonic components are positively affected by the design favoring bST. However, few investigations have been done on beef cows. It was hypothesized that beef cows treated with bST, the day timed AI (TAI) or seven days after TAI, have higher conception rates and the morphology of the endometrial glands and the proportion of steroidogenic luteal cells are altered by such treatment. The present study aimed to evaluate the effect of bST at a dose of 250 or 500mg, the day of TAI, the conception rate at 30 days of gestation (Experiment 1); verify the effects of application of 500mg of bST, seven days after TAI, the conception rate at 30 days of gestation (Experiment 2) and investigate the effects of bST in the proportion of steroidogenic luteal cells and morphometry of the endometrial glands (Experiment 3). In Experiment 1, Nelore cows (n=587) received an intravaginal device containing progesterone (1g; DIB®) associated with an intramuscular (IM) injection of estradiol benzoate (2mg; Gonadiol®). The devices were removed after eight days, when cows were treated with D-cloprostenol (0.530 mg; Ciosin®) and equine chorionic gonadotropin (300UI; Novormon®) and after 24 hours received estradiol benzoate (1 mg; Gonadiol®), via IM. After 30 hours of the last injection (D0) females were inseminated and received 5ml of saline (Control Group; n=194) or somatotropin (Boostin®) at a dose of 250mg (Group bST 250; n=197) or 500mg (Group bST 500; n=196), subcutaneously (SC). Pregnancy diagnosis was performed 30 days after TAI by ultrasonography. In Experiment 2, Nelore cows (n=243) received the Experimento1 similar protocol and were inseminated on D0. In D7 received 5ml of saline (Control Group; n=124) or somatotropin (Boostin®) at a dose of 500mg (Group bST 500; n =119) subcutaneously...(Complete abastract click eletrononic acess below)
Keywords: Bovino de corte; Inseminação artificial; Somatotropina; Endometrio; Corpo lúteo; Embryonic development